Patterns of Care for Radiotherapy in Vulvar Cancer: A Gynecologic Cancer Intergroup Study. Issue 1 (1st January 2009) - Gaffney, David K.; Du Bois, Andreas; Narayan, Kailash; Reed, Nick; Toita, Takafumi; Pignata, Sandro; Blake, Peter; Portelance, Lorraine; Sadoyze, Azmat; Potter, Richard; Colombo, Alessandro; Randall, Marcus; et al.
Abstract : Background: This study aimed to describe radiotherapeutic practice in the treatment of vulvar cancer in member study groups of the Gynecologic Cancer Intergroup (GCIG). Methods: A survey was developed and distributed to representatives of the member study groups of the GCIG, targeting the use of radiotherapy (RT) in vulvar cancer. Results: Thirty-two surveys were returned from 12 different cooperative groups. The most common indications for neoadjuvant RT include unresectable disease or International Federation of Gynecology and Obstetrics stage ≥III. For the neoadjuvant treatment of vulvar cancer, pelvic doses were 48.2 ± 5.0 Gy (mean ± SD). The upper border of the pelvic field was L4/5 in 4, L5/S1 in 12, and not specified in 4. Of 21 groups that perform neoadjuvant RT, 17 use concomitant chemotherapy and 4 individualize treatment. Weekly cisplatin was the most commonly used chemotherapy. For the neoadjuvant RT treatment of the inguinal region, doses were 49.9 ± 5.5 Gy (mean ± SD). Sixteen of 18 groups used computed tomographic simulation for planning. After initial surgery, the most common indications for RT included positive lymph nodes or positive margins. Chemotherapy was not routinely used after surgery. Conclusions: Doses of RT among GCIG members are similar; however, the indications for treatment, treatment fields, and use of chemotherapy differ somewhat between groups. This is likely due to the rarity of the disease. The lack of randomized trials may contribute to the absence of a broadly accepted standard. This underscores the importance of international cooperation as in GCIG to gather more reliable data for uncommon tumors in gynecologic oncology.